2015
DOI: 10.1007/s00383-015-3712-1
|View full text |Cite
|
Sign up to set email alerts
|

The current strategy for urachal remnants

Abstract: Conservative follow-up is recommended for UR under 1-year old except when there are repeated infections. The umbilical approach is enough for infants. Laparoscopic surgery is recommended in older children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 18 publications
1
30
0
1
Order By: Relevance
“…10 According to Sato et al, the most common symptom is umbilical granulation in infants and abdominal pain in older children. 11 It has been reported that malignancy may develop in later years. 12 Infected urachal cysts rarely rupture and can rapidly become symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…10 According to Sato et al, the most common symptom is umbilical granulation in infants and abdominal pain in older children. 11 It has been reported that malignancy may develop in later years. 12 Infected urachal cysts rarely rupture and can rapidly become symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…UAs can be diagnosed by US. Two studies reported 12 and 27 cases of UA, in which all of their patients were diagnosed by US with limited usage of CT scans and magnetic resonance imaging (MRI) which were only used for further detailed anatomy [14,15]. However, Widni et al reported US as having 79% sensitivity, 30% specificity, and 83% positive predictive value in diagnosing UAs [16].…”
Section: Discussionmentioning
confidence: 99%
“…Complete surgical excision is considered the treatment of choice, given the risk of malignant transformation and the high recurrence rate after simple drainage, which Mesrobian et al reported at 39% [17]. The excision can be done either by an open laparoscopic approach [14,15] or a robotic assisted laparoscopic surgery [18]. Bertozzi et al reported 12 cases of UA that were treated by laparoscopic or laparoscopic-assisted surgery [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, malignant trans-formation may occur [2,14,17]. Other urachal anomalies are diagnosed in early childhood, needing surgery when bladder infections are recurrent [19].…”
Section: Discussionmentioning
confidence: 99%